2017
DOI: 10.1002/fuce.201600038
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Surface Oxide Layer of Fe‐Cr‐Al Alloy with Coating Materials for SOFC Applications

Abstract: We investigated the treatment of Fe‐Cr‐Al alloy for application in solid oxide fuel cells (SOFCs). The electrical resistance of the Al2O3‐based surface oxide layer on the alloy decreased and was stable when La0.6Sr0.4Co0.2Fe0.8O3 (LSCF), La0.8Sr0.2MnO3 (LSM), LaNi0.6Fe0.4O3 (LNF), or Pr0.8Sr0.2MnO3 (PrSM) were first coated on the alloy and heat treated at 700 °C in air. The activation energy, calculated from the resistance, also suggested that the surface oxide became more conductive with treatment. The surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Porous alloy was used for the measurement to avoid detachment of the LSCF coating from the alloy surface and obtain stable resistance, and also to decrease the resistance to closer to the practically required value. In this study, it was confirmed that the interfacial resistance for the porous alloy was roughly ten times lower than that for the dense alloy plate because of the increased contact area, 11,12 although it may change depending on the porosity of the alloy and penetration depth of the paste.…”
Section: Methodssupporting
confidence: 52%
See 2 more Smart Citations
“…Porous alloy was used for the measurement to avoid detachment of the LSCF coating from the alloy surface and obtain stable resistance, and also to decrease the resistance to closer to the practically required value. In this study, it was confirmed that the interfacial resistance for the porous alloy was roughly ten times lower than that for the dense alloy plate because of the increased contact area, 11,12 although it may change depending on the porosity of the alloy and penetration depth of the paste.…”
Section: Methodssupporting
confidence: 52%
“…in normal cases, relatively large-size crystalline γ-Al 2 O 3 grew in various directions with much less Sr content (<1 at.%). 11,12 It is assumed that Al ions diffusing outward through γ-Al Figure 5 shows the STEM image and EDS mapping after the test at 900 • C for 3 h in air. The surface oxide layer was composed of aluminum oxide with 5.9 at.% Sr content, and the thickness was approximately 400 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Advantages of metal‐supported cells over conventional all‐ceramic cells also include low‐cost structural materials (stainless steels) and mechanical ruggedness, showing high potential of MS‐SOCs for mobile and/or intermittent application. In recent years, substantial development of metal‐supported fuel cells (MS‐SOFCs) has resulted in excellent performance and durability, and demonstration of the unique advantages discussed above . Several challenges with MS‐SOFCs have also been identified, and these are also expected to be relevant for electrolysis operation and must be addressed in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the Ni cermet anode needs to be optimized to improve coking resistance. Therefore, substantial efforts have been attempted, such as metal alloying, changing ionic conductor phase, or modifying to the Ni‐based anode surface or the bulk . As we know, coking is caused due to the pyrolysis of hydrocarbon on Ni surface.…”
Section: Introductionmentioning
confidence: 99%